Contact Angle Analysis: Contact Angle Analysis for the Prediction of Defect States of Graphene Grafted with Functional Groups (Adv. Mater. Interfaces 19/2018). Issue 19 (9th October 2018) - Bong, Jihye; Park, Ju Hyun; Lim, Taekyung; Kang, Seok Ju; Kwak, Sang Kyu; Ju, Sanghyun
Abstract : The wettability of graphene shows a correlation with the defect density, which could be quantitatively estimated by observing the shape of a water drop on the graphene surface through contact angle measurements. More details can be found in article number1800166 by Jihye Bong, Sang Kyu Kwak, Sanghyun Ju and co‐workers.